Clinical and Molecular Characterization of Feline Sporotrichosis in the Brazilian Amazon: PCR-Based Identification of Sporothrix brasiliensis - Nayara Fátima Lazameth-Diniz; Danielle Barreto de Almeida; Flávia da Silva Fernandes; Adriana Oliveira da Silva Queiroz; Érica Simplicio de Souza; Kátia Santana Cruz; Ani Beatriz Jackisch Matsuura; Hagen Frickmann; João Vicente Braga de Souza (Animals)
Sporotrichosis is a zoonotic fungal infection with increasing incidence in the Brazilian Amazon, primarily affecting domestic cats and posing risks to human health. This study characterized the clinical and epidemiological profiles of 29 feline sporotrichosis cases in Manaus and optimized molecular diagnostic methods for Sporothrix species identification. Most affected cats were young (86.2% aged 1–3 years), male (82.7%), and free-roaming or semi-indoor (44.8% each), frequently presenting cutaneous lesions localized at the nasal planum (23.3%), ears (7%), eyes (2.3%) and other facial areas (18.6%). Three DNA extraction methods were compared; the phenol–chloroform protocol yielded the highest DNA concentration and purity, and ITS1–ITS4 primers showed an adequate sensibility for PCR detection. In silico RFLP profiles using common restriction enzymes showed limited discriminatory power among Sporothrix species. ITS sequencing of four high-quality amplicons confirmed all isolates as Sporothrix brasiliensis. Antifungal susceptibility testing of all isolates revealed geometric mean MICs of 0.25 µg/mL for ketoconazole, 0.57 µg/mL for itraconazole, 7.27 µg/mL for amphotericin B, and 64 µg/mL for fluconazole, respectively. These findings provide clinical, molecular, and therapeutic information supporting the diagnosis and surveillance of feline sporotrichosis in the Amazon, reinforcing the need for ongoing veterinary and public health monitoring.